Search for top squark pair production in a final state with two tau leptons in proton-proton collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2020)
A search for pair production of the supersymmetric partner of the top quark, the top squark, in proton-proton collision events at s = 13 TeV is presented in a final state containing hadronically decaying tau leptons and large missing transverse momentum. This final state is highly sensitive to high-tan beta or higgsino-like scenarios in which decays of electroweak gauginos to tau leptons are dominant. The search uses a data set corresponding to an integrated luminosity of 77.2 fb(-1), which was recorded with the CMS detector during 2016 and 2017. No significant excess is observed with respect to the background prediction. Exclusion limits at 95% confidence level are presented in the top squark and lightest neutralino mass plane within the framework of simplified models, in which top squark masses up to 1100 GeV are excluded for a nearly massless neutralino.
Keywords: Hadron-Hadron scattering (experiments); Supersymmetry; Top physics; MEASURING MASSES; MODEL; PHENOMENOLOGY; SUPERSYMMETRY; EXTENSION; INVARIANT; ENERGY